Calculation of Price Reduction in International Sale of Goods Contracts - Fišer Šobot Sandra (LeXonomica, 2017)
Price reduction is a part of The United Nation Convention on Contract for the International Sale of Goods remedial scheme and is available to the buyer if delivered goods are not in conformity with the sales contract. Price reduction is a very suitable remedy and offers numerous advantages in comparison to other remedies. It is widely used in practice. However, diverging scholarly interpretations and relevant case law show that there are some ambiguities and uncertainties as to its calculation. This paper will examine relevant issues regarding the calculation of price reduction.